CFD simulation of a large-scale VAWT- Evaluation of the rotor performance for a gradient wind profile - Boberg, Mikaela (My University, 2019)
SeaTwirl is a developer of a large-scale vertical axis wind turbine and in previous aerodynamic studies of the rotor performance a uniform wind profile have been used. However, the characteristics of the landscape result in friction for the wind flow and the shear stresses generates a gradient wind profile. Hence, this study aims to investigate how the velocity gradients affect the rotor performance and how the efficiency may be increased by alternating the rotor design such as elevating the rotor position or the blade height. The numerical domain consisted of a 2D horizontal cross-section of three airfoils, the tower and struts were excluded. The k-! SST turbulence model was used to solve the unsteady RANS equations. The result showed that the difference in estimated power generation between the usage of a uniform compared to a gradient wind profile deviated with 5%. The result also indicated that it was more beneficial to increase the rotor swept area instead of increasing the rotor position. The study showed that the tip-speed-ratio drastically affected the forces acting on the blades and that these effects are prominent for large-scale vertical axis wind turbines due to the fixed blade configuration. This method was a good implement to obtain a deeper knowledge of the forces acting over the whole blade length. However, performing a full 3D model of the wind turbine would be desirable to validate the 2D method.
Keywords: Strömningsmekanik och akustik; Hållbar utveckling; Energi; Fluid Mechanics and Acoustics; Sustainable Development; Energy